Botulinum Toxin as a Biological Warfare Agent: Poisoning, Diagnosis and Countermeasures - Pohanka, Miroslav (Mini reviews in medicinal chemistry, 2020)
Botulinum toxin is a neurotoxin produced by Clostridium botulinum and some other relative species. It causes a lethal disease called botulism. It can enter the body via infections by Clostridium (e.g. wound and children botulism) or by direct contact with the toxin or eating contaminated food (food-borne botulism). Botulinum toxin is also considered as a relevant biological warfare agent with an expected high number of causalities when misused for bioterrorist or military purposes. The current paper surveys the actual knowledge about botulinum toxin pathogenesis, the manifestation of poisoning, and current trends in diagnostics and therapeutics. Relevant and recent literature is summarized in this paper.
Keywords: botulinum toxin; botulismus; poisoning.; Botulism; Biological Warfare Agents; lidé; biological warfare agent; diagnosis; botulotoxiny; biologické bojové látky; detection; Acetylcholine; botulism; Clostridium botulinum; Botulinum Toxins; antiserum; Humans